Analysis of Heart Rate Variability and Cardiac Autonomic Nerve Remodeling in Streptozotocin-induced Diabetic Rats - Li, X.; Jiang, Y.-H.; Jiang, P.; Lin, H.-Q.; Yang, J.-L.; Ma, D.-f.; Wang, X.; Yang, C.-H. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: Diabetes mellitus (DM) is associated with both cardiovascular and autonomic nervous system dysfunction. Spectral analysis of heart rate variability (HRV) can be used to monitor changes in response to autonomic innervation and stimulation of the heart. In this study, conducted in a rat model of diabetes, HRV and changes in associated neurotransmitters and neurotrophic factors in the right atrium (RA) were monitored.Methods: Diabetes was induced by streptozotocin (STZ) (60 mg/kg) in male Wistar rats, and HRV data were collected for 10 weeks by telemetry. Time and frequency domains of HRV data were analyzed using established metrics. The levels of various neural enzymes in the RA were determined by enzyme-linked immunosorbent assay (ELISA) and immunofluorescence to characterize autonomic nerve remodeling. Insulin and methycobal were used to block the effects of STZ.Results: HRV parameters reflecting parasympathetic tone (SDNN, RMSSD and HF domains) sharply decreased in the first 3 weeks after STZ administration; measures of sympathetic tone (SDANN) increased. After a series of adjustments, cardiac autonomic nerve innervation reached a new equilibrium, with a dominance of sympathetic tone. RA levels of tyrosine hydroxylase (TH) increased, and choline acetyltransferase (ChAT) decreased, indicating autonomic nerve remodeling. Levels of growth associated protein-43 (GAP43) and nerve growth factor (NGF) increased during the period of diabetes-induced cardiac-nerve damage; however, the level of ciliary neurotrophic factor (CNTF) decreased. The physical condition and indexes of rats were normalized in different degree after administration of the insulin and methycobal, but not completely recovered.Conclusion: STZ-induced diabetes was associated with cardiac autonomic nerve dysfunction at both the organ and molecular levels. Parasympathetic nerves exhibited severe damage and/or weak recovery; remodeling of sympathetic nerves predominated during 10-weeks of STZ-induced diabetes.
Keywords: diabetes; heart rate variability; autonomic nerve remodeling; neurotransmitter rate-limiting enzyme; CNTF; NGF; GAP-43; right atrium